Efektifitas Komisi Pengawas Persaingan Usaha (KPPU) dalam Upaya Penyelesaian Kasus Praktek Monopoli dan Persaingan Usaha Tidak Sehat - Rezmia Febrina (Fakultas Hukum Universitas Riau, 2018)
The position of KPPU in carrying out its functions of authority becomes a very important matter to be discussed. Given Law No. 5 of 1999 has given KPPU a very large authority resembles the authority of the Judicial Institution (quasi judicial). The authority of the commission that resembles the judiciary is the authority of the commission to carry out the function of investigating, examining, deciding and ultimately imposing administrative punishment on the case he terminates. Likewise, the authority to impose a sanction of compensation or a fine to the reporting business actor. The type of this research is normative juridical research, which is a descriptive documentary study. This legal research is done by examining the library materials or secondary data only, which is also called legal research literature. The effectiveness of the Business Competition Supervisory Commission (KPPU) as an Independent institution established by the government for the settlement of cases of business competition practices has been known in Indonesia since 1999, this can be seen with the issuance of Law Number 5 Year 1999. With so many cases of business competition demanding KPPU that has the duty and authority to work hard to solve the case of the business competition. A decision of KPPU is deemed to have permanent legal power, if The business actor does not object to the KPPU's decision within the stipulated timeframe (Article 44 paragraph (3) and Article 46 paragraph (1) of the Antimonopoly Law; The reasons for the objection to KPPU's Decision shall be rejected by the District Court and within the stipulated period of time the business actor has not filed an appeal to the Supreme Court (Article 45 paragraph (3) of the Antimonopoly Law, and; The reasons for appeal filed by a business actor (reported) are rejected by the Supreme Court.